UPAYA MENINGKATKAN HASIL BELAJAR DAN KETERAMPILAN MENULIS KALIMAT SARAN MELALUI MODEL PEMBELAJARAN MULTISENSORI - Khoimatun, Khoimatun; Rukmini, Piyantina; Padlilah, Mutimatul (Transpublika Publisher, 2023)
The implementation of the multisensory learning approach offers an alternative method to enhance students' writing skills and overall learning outcomes in the Indonesian language subject. After conducting observations, it was discovered that the third-grade students at SDIT As-Salafiyah had low learning outcomes and writing skills in the Indonesian language subject for the 2021/2022 academic year. The inadequate understanding of suggested sentences by students and suboptimal learning management by the teacher were identified as the main causes for these low outcomes. This study employed Classroom Action Research (CAR), which comprised four components: Planning, Action, Observation, and Reflection. In the first cycle, student learning outcomes reached 52.38%, and in the second cycle, it increased to 85.71%, indicating that the mastery of learning outcomes had achieved the expected classical completeness of 80%. In terms of writing skills, the first cycle yielded a score of 1280 with a percentage of 60.95%, indicating a moderate level of proficiency. However, in the second cycle, the score rose to 1900 with a percentage of 90.48%, indicating a high level of proficiency. The teacher's activity observation sheet during the implementation of the multisensory learning approach showed a 62% rating in the first cycle, which improved to 86% in the second cycle, indicating a very good performance. Therefore, it can be concluded that the application of the multisensory learning model effectively enhances students' learning outcomes and writing skills.